Physiological strategies of Eichhornia crassipes (Mart.) Solms to tolerate Cr6+ accumulation, compared to a sensitive species Pistia stratiotes L. - Taufik Taufikurahman; Andira Rahmawati; Muhammad Arief Ardiansyah; Dea Prianka Ayu Ilhamsyah; Serafina Rosanti (Jurnal Ilmu Lingkungan, 2020)
Chromium in the form of hexavalent chromium (VI) has been used in some industry including leather tanning industry. The chemical has been known to be harmful to  living organisms. Therefore, it is important to treat wastewater from leather tanning industry before being discharged to the environment. The aim of this study is to examine ecophysiological strategies of  waterhyacinth (Eichhornia crassipes)  to tolerate Cr6+ accumulation in its tissue, compared to sensitive species water lettuce (Pistia stratiotes).  The plants  were cultivated in containers containing Hoagland medium and treated with some variation of Cr6+ concentrations of Cr6 i.e. 0, 40, 80 and 120 ppm for 14 days. Some parameters including CAT (catalase), Ascorbate peroxidase (APX), chlorophyll concentration and proline  in the plants were measured. The biomass yield of plant in Cr6+ stress was negative (-0.732 to -1.84 g/week) which indicated both E. crassipes and P. stratiotes  reduced their growth. The higher the concentration of Cr6+, the lower the chlorophyll contents in the leaves. The lowest of chlorophyll content was in 120 ppm (0.15 mg/g in P. stratiotes  and 0.12 mg/g in E. crassipes). The highest of CAT activity in E. crassipes was 109% in 40 ppm Cr6+, while in P. stratiotes  was 76% in 120 ppm. Proline content in both E. crassipes and P. stratiotes  were not different significantly. In general, E. crassipes plants have the ability to adapt to Cr6+ stress better compared to P. stratiotes which was severely damaged when grown in high Cr6+ concentration. Both plants can remediate waste fairly well  (level of elimination 62-68%) during the exposure period of 14 days to Cr6+ solution.